Analisis Dinamika Komunikasi Kelompok Penggemar K-Pop Generasi ke-4 (STAY, ATINY, dan MOA) dalam Menanggapi Fanwars di Media Sosial Twitter - Arimbi Febriani Ramedi Putri; Hedi Pudjo Santosa; Amida Yusriana (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The rapid development of K-Pop is shown by the increasing number of fans in the K-Pop 4th generation’s fandom especially STAY, ATINY, and MOA with the strength within three fandoms shown by the solidarity of fans in carrying out activities in support of their idols on Twitter and participate in social activities. The sense of kinship in the fandom is also felt by supporting and encouraging each other. However, fandoms are often involved in fanwars or fights between fandoms by insinuating, berating, and bullying other fans and their idols. This study aims to see themes displayed by fans in responding to fanwars on Twitter and to find out how the dynamics of group communication in STAY, ATINY, and MOA in responding to fanwars on Twitter. The method used is descriptive qualitative with an interpretive approach. The theories used in this research include the theory of group communication dynamics and participatory culture. The data obtained using the interview method with several informants and observations made online. The themes found within three fandom in responding to fanwars on Twitter is on the dynamics of group communication: interaction analysis, direction of communication, and communication networks. The themes in participatory culture include: message consumption and participation. This research shows that in the STAY, ATINY, and MOA fandoms there are several types of fans based on their responses and participation in fanwars with the direction of communication between each fan running in two directions and the communication network they have is a chain pattern and all channel pattern. They also use social media, especially Twitter, to the maximum extent, as a platform for their activities as fans specifically to dig up information about the fanwars that occurred.